Mitigating aflatoxin contamination in maize: Breeding for stable resistant cultivars - Oppong, Allen; Appiah Jnr, Kofi; Appiah-Kubi, Zippora; Adu-Amoah, Richard; Adu-Dapaah, Hans (Frontiers in Horticulture, 2022)
Maize(Zea mays) is a major cereal crop for both plant and animal nutrition worldwide. The production and consumption of maize is adversely affected by aflatoxin contamination resulting in reduced grain quality with high health risk to consumers. Unsafe Aflatoxin levels above 20ppb have been reported in maize from farmers’ fields in Ghana. A study was undertaken to evaluate the yield and aflatoxin contamination resistance stabilities of selected hybrids being developed in Ghana. Eighteen maize genotypes;fourteen hybrids with the following code names:GH01, GH02, GH03, GH04,GH05,GH06, GH07,GH08,GH09,GH10,GH11,GH12,GH13,GH14; and four local checks; Etubi,Obotantim,Tintim, Mamaba were evaluated across six environments. Artificial inoculation was done randomly using the side needle injection method 14 days after midsilk at a concentration of 9×107conidia/ml. After harvest levels of aflatoxin in the harvested grains were determined using high performance liquid chromatography(HPLC). Data analysis showed that genotypic effects and environmental effects on some traits were consistently significant across environments which mean that there was useful variation among the genotypes which could be utilized for development of hybrids. Non-significant genotype by environment interaction effects for grain yield suggests that a promising genotype selected in one of these locations will also be suitable for production in the other locations in the same agro-ecological zone. GGE biplot analyses provided clear bases for determining stability and performance of the hybrids. Two hybrids have the potential for production in Ejura, Fumesua, Ohawu, Akumadan and Kpeve and similar agro-ecological zones. GH04, GH10 and GH01 were lowest yielding but GH10 was most stable. GH05 was identified as the most promising for production in Ejura, Ohawu and Akumadan. Again GH08 was the Vertex genotype for Wenchi environment. Ejura located in the transition zone, was identified as the ideal testing environment for the hybirds. Most of the hybrids showed low levels of aflatoxin accumulation below 20ppb despite artificial inoculation. The study revealed GH01, GH05 and GH08 as the most stable among the top yielding hybrids with aflatoxin levels of 11.9 ppb, 14.3 ppb and 3.8 ppb respectively after artificial inoculation. which can be considered for cultivation as varieties to help mitigate aflatoxin contamination in maize in Ghana and beyond